2014
DOI: 10.1016/j.neulet.2014.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of aquaporin-4 deficiency in a mouse model of severe global cerebral ischemia produced by transient 4-vessel occlusion

Abstract: Astrocyte water channel aquaporin-4 (AQP4) facilitates water movement across the blood–brain barrier and into injured astrocytes. We previously showed reduced cytotoxic brain edema with improved neurological outcome in AQP4 knockout mice in water intoxication, infection and cerebral ischemia. Here, we established a 4-vessel transient occlusion model to test the hypothesis that AQP4 deficiency in mice could improve neurological outcome following severe global cerebral ischemia as occurs in cardiac arrest/resusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 26 publications
(32 reference statements)
2
33
0
Order By: Relevance
“…Upregulation of AQP4 may occur during trauma-induced cytotoxic edema in rats, and the outcome becomes worse with the upregulation of AQP4 (8), whereas edema is less severe with the downregulation or knockout of AQP4 during cytotoxic edema (20,21). In addition, the attenuation of brain edema was observed in an AQP4-knockout mouse model, suggesting that the depletion of AQP4 may be protective during cytotoxic brain edema (22). However, most of the data currently available on the role of AQP4 in ischemic brain edema are based on small animal models such as mice and rats.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of AQP4 may occur during trauma-induced cytotoxic edema in rats, and the outcome becomes worse with the upregulation of AQP4 (8), whereas edema is less severe with the downregulation or knockout of AQP4 during cytotoxic edema (20,21). In addition, the attenuation of brain edema was observed in an AQP4-knockout mouse model, suggesting that the depletion of AQP4 may be protective during cytotoxic brain edema (22). However, most of the data currently available on the role of AQP4 in ischemic brain edema are based on small animal models such as mice and rats.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported greatly improved outcome in AQP4 knockout mice following focal ischemia produced by permanent MCAO [16], and more recently, improved outcome in AQP4 knockout mice following global ischemia produced by transient carotid artery occlusion [1, 10]. Also, several correlative studies reported reduced cerebral edema following ischemia with reduced AQP4 expression, including propofol and edaravone administration, protein kinase C activation [4], hypertonic saline administration [30], and endothelin-1 overexpression [13].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the complexities of cytotoxic and vasogenic mechanisms, the main finding of this study was a small beneficial effect of AQP4 deletion in TBI. The beneficial effect was very small compared with the robust beneficial effects of AQP4 deletion in water intoxication, a model of pure cytotoxic edema 4 , or in focal 32 or global33,34 cerebral ischemia, where cytotoxic edema predominates. The small beneficial effect of AQP4 deletion in the CCI model here may be the consequence of mixed cytotoxic/vasogenic edema mechanisms in which AQP4 has opposing actions.…”
mentioning
confidence: 90%